Analysis of Pain and Depression Level in Knee Osteoarthritis Patients at Islamic Hospital Siti Rahmah - Anissa, Mutiara; Aswad, Fauziah Amelia; Darmayanti, Anita; Putra, Eko Perdana; Deny, Fitra (Muhammadiyah Medical Journal, 2025)
Background: Knee osteoarthritis is a degenerative joint disease involving slow cartilage damage. Pain is the main symptom of osteoarthritis, and it causes patients to feel desperate, which further affects their emotional well-being, leading to depression. Purposes: This study aims to determine the relationship between the level of pain and the level of depression in knee osteoarthritis patients at RSI Siti Rahmah Padang. Methods: The materials used in this study are medical records, the Patient Health Questionnaire (PHQ)-9, and the Visual Analog Scale (VAS). This research uses univariate data analysis presented in the form of frequency distribution. Bivariate data analysis uses the chi-square, cross-sectional technique with 75 respondents. Results: Knee osteoarthritis patients with severe pain mostly also experience severe depression, with a percentage of 11%; patients with moderate pain mostly also experience moderate depression, with a rate of 14%; and patients with mild pain also experience mild depression, with a percentage of 10%. Bivariate analysis results show that there is a relationship between the level of pain and the level of depression with a value of p <0.05 (p = 0.000). Conclusion: This study found a relationship between the level of pain and the level of depression in knee osteoarthritis patients at RSI Siti Rahmah Padang.